Dynamic selection-based method for physical-based deformation - Mohd. Suaib, Norhaida (2006)
Deformable object modeling is a modeling method where one changes the shape of an object. Some application such as virtual surgery requires deformations that are based on physical justifications, usually known as physical based deformation. In addition to physical realism, interactive feedback is required so that it can be applicable in virtual surgery. If interior structure behavior or appearance plays a vital role in a deformation system, the deformable object should be represented as volumetric object. One can represent volumetric object using structured or unstructured geometric mesh. Two popular physical based deformation methods are finite element method and mass-spring systems. Finite element methods have higher deformation accuracy compared to mass-spring system but at a much higher computation cost.